Association between liver fibrosis and appendicular skeletal muscle mass during antiviral therapy in chronic hepatitis B. Issue 11 (November 2020) - Kim, Kyung Hyun; Joo, Dong Jin; Lee, Yong-ho; Kim, Beom Kyung; Park, Jun Yong; Kim, Do Young; Ahn, Sang Hoon; Han, Kwang-Hyub; Kim, Seung Up
Abstract: Background and aims: Sarcopenia is associated with fibrotic burden in patients with chronic hepatitis B. We investigated the dynamic association between fibrosis changes and appendicular skeletal muscle mass during antiviral therapy in patients with chronic hepatitis B. Methods: Between 2015 and 2018, chronic hepatitis B patients who received paired transient elastography to assess fibrotic burden in the liver and bioelectrical impedance analysis to assess appendicular skeletal muscle mass were recruited retrospectively. The sarcopenia index was calculated as total appendicular skeletal muscle mass/body mass index. Significant liver fibrosis was defined as a liver stiffness value≥8 kPa. Results: In total, 223 (53.7%) received antiviral therapy, whereas 192 (46.3%) did not. Appendicular skeletal muscle mass decreased significantly in the antiviral therapy group (mean 21.16→21.00 kg, P  = 0.01), but not in the non-antiviral therapy group (mean 20.77→20.64 kg, P  = 0.134). In a subgroup with significant liver fibrosis, similar findings were observed (mean 20.73→20.54 kg in antiviral therapy group, P  = 0.037; mean 21.39→21.07 kg in the non-antiviral therapy group, P  = 0.097). Older age, male gender, higher body mass index, and higher aspartate aminotransferase were significantly associated with the increased risk of appendicular skeletal muscle mass reduction (≥5% from the baseline). Conclusions: Appendicular skeletal muscle mass significantly decreased during antiviral therapy in patients with chronic hepatitis B patients.